Analisis keterampilan menulis menggunakan unggah-ungguh basa jawa kelas V Sekolah Dasar - Murni Evi Pratama; Joko Daryanto; Sandra Bayu Kurniawan (Universitas Sebelas Maret, 2023)
Abstract. This study aims to describe students' writing ability in writing using Javanese language. This research uses a qualitative approach that produces descriptive data from people or an observation in writing or orally. The subjects used in this study were fifth grade students and teachers of SDN Mangkubumen Lor No.15 in the 2022/2023 school year. Data collection techniques used document studies of student essay results, interviews with fifth grade teachers and observations of the learning process. The data analysis technique used the Miles and Huberman analysis model. Based on the results of data analysis, it was found that the writing skills of fifth grade students of SDN Mangkubumen Lor No.15 were still low. Out of 13 students, 5 students are in the sufficient category and 8 of them are in the insufficient category because many indicators in writing skills using Javanese bases have not been met. Problems that arise related to students' writing skills using Javanese bases are students' mastery and understanding of Javanese bases are still very low, the vocabulary/lexicon owned by students is very minimal, the learning process is less interesting and interactive and the low interest of students in participating in Javanese language learning.